Restoration of function of reciprocal walking in children with spinal cord pathology - Chernyshova, Irina (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Physical rehabilitation of children with spinal cord pathology remains one of the most complicated and advanced methods in medical and social rehabilitation providing extensive use of orthoses systems. Objective: To determine the effectiveness of the orthosis with reciprocal mechanism for the recovery of walking function in children with consequences of vertebral and spinal cord injuries, disease and congenital abnormalities of the spinal cord. Methods: A five-year comparative analysis of the results of a clinical, radiological and physiological study in 31 children with the consequences of vertebral-spinal trauma, disease and congenital abnormalities of the spinal cord was carried out. Patients of the main group (17 children) rehabilitated with reciprocal orthosis according to the developed program of rehabilitation. Children in the control group (14) used the conventional locking orthosis systems. Results: greater efficiency of using of the orthosis with the reciprocal mechanism for the rehabilitation of children with pathology of the spinal cord was established comparing to conventional locking orthosis systems. Reciprocal walking in orthoses with reciprocal mechanism facilitated decreasing an abnormal muscle tone, increasing strength of preserved musculature, the compensation level of the motor deficits, general motor activity and independence of the patients from the assistance which has led to the recovery of the functions of self-walking in reciprocal orthosis in 76.5 % of children. In the control group an independent walking has not been mastered by none of the patients. Conclusion: The efficiency of reciprocal orthosis in rehabilitation of patients with lack of walking function due to pathology of the spinal cord allows you to recommend the proposed system of rehabilitation and these orthoses for increasing the effectiveness of rehabilitation measures.